2006
DOI: 10.1016/j.ejor.2004.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and heterogeneity of railway services

Abstract: Reliability is one of the key factors in transportation, both for passengers and for cargo. This paper examines reliability in public railway systems. Reliability of railway services is a complex matter, since there are many causes for disruptions and at least as many causes for delays to spread around in space and time. One way to increase the reliability is to reduce the propagation of delays due to the interdependencies between trains. In this paper we attempt to decrease these interdependencies by reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 8 publications
0
82
0
1
Order By: Relevance
“…Kozan and Burdett (2005), Vromans et al (2006) and Harrod (2009) have shown that SRT has a significant impact on capacity analysis, for instance, a slight change in SRT can have remarkable effect on the amount of capacity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kozan and Burdett (2005), Vromans et al (2006) and Harrod (2009) have shown that SRT has a significant impact on capacity analysis, for instance, a slight change in SRT can have remarkable effect on the amount of capacity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One way to increase reliability is to reduce the propagation of delays due to interdependencies between trains [38]. For example, the interdependencies can be decreased by reducing the running time differences per track section and creating more homogeneous timetables.…”
Section: Recent Railway System Breakdownsmentioning
confidence: 99%
“…In fact, an exponential relationship exists between adding trains to a congested network and the expected level of network performance [12]. For the time being, the focus is on solving small primary disturbances, mainly because no timetable is robust enough to handle large disruptions without drastic realtime traffic adjustments [38].…”
Section: Recent Railway System Breakdownsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vromans, Dekker and Kroon [14] describe an analytical method to evaluate how the minimum gap between two trains affects reliability. An adequate method of evaluating how a system reacts to delays and how changes affect this is simulation, as described for example in [3,10].…”
Section: Definition Of Track Capacitymentioning
confidence: 99%